Pengolahan Material Serat Alami Menggunakan Enzim Mikrobiologi untuk Media Ekspresi Seni Dua Dimensi - Muksin Muksin (Journal of Visual Art and Design, 2007)
One of the alternative media, which is potential to be developed is the use of natural fiber materials from the environment (indigenous material). This natural fiber in foreign country such as Thailand, Japan, United States has crossed the threshold of the quality as a work of art that create by an artist. Meanwhile in Indonesia it is still brand new to be develop as a media of art expression. Indeed, art paper has already developed in Indonesia, but it is still a boundary production of pieces of paper that will be directly applied as a handicraft media. Moreover, the preparation process is still using the conventional method using chemical materials such as NaOH, Hypochloride, Boric acid, Chlorin, H2O2, etc., which burden the environment. Therefore an alternative, environmental friendly process is necessary to be developed to exploit natural fiber materials as a media of art expression. For this reason in this project a research on fiber-pulping process using xylanase enzyme has been carried out. The use of xylanase is enable to decrease chlorin consumption and reduce  chloro-organic concentration in pulp and waste, that also means a reduction in  production cost. The pulp was then used to make a paper to be tested for its quality by the Center for Pulp and Paper (Balai Besar Pulp dan Kertas, BBPK). This research resulted in a) enzyme formulations for the fiber-pulping and preparation from variety of fiber materials: banana's stalk, the abacca, hyacinth, straw, pineapple fiber and gold cocoon, b) data of paper quality, and c) work of arts from fiber/pulp material. In conclusion, enzyme can be applied in fiber-pulping process for lower impact on the environment and the workers.